Versando com um grevear entre políticas de expansão no IFES - Martins, Giselly Ferreira (2016)
This dissertation approaches the grevear practices which emerge amid the expansion process of the Federal Network of Professional Education, Science and Technology in Espirito Santo. Grevear, in this work, is seen as an ethos that produces interference in management practices, working conditions and ongoing training processes in Professional Education. The survey was made with IFES workers, by conducting 10 interviews guided in a semi-structured script open to the intervention of the participants. These interviews aimed to access the grevear experience developed by IFES workers and they allowed to perceive that the way the expansion of the Federal Network of Professional Education has been carried out has been producing precariousness and a state of dereliction which, in turn, are effects of the expansion of privatization policies of public education, that transfers public resources to private entities. The grevear experience interferes in the accelerated times, making stops at privatizing and performative movements and constituting itself as care practice as well. The reports of IFES workers point out that grevear is to produce moments of disutility in the performative policies that circulate in the public schools.